RANCANG BANGUN SISTEM PENGUKURAN KUALITAS ANTENA Very High Frequency (VHF) UNTUK KOMPETISI ANTENA TINGKAT NASIONAL - , FERLY SOPAN ATMAJA; , Prof. Ir. Sunarno, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In order to measure the transmit quality of VHF antenna, has been set up a measurement system. For further purpose, this system can also applied for national scale antenna competition. This system consist of main components which are Field Strength Meter (FSM), Antenna Pattern Analyzer (APA), Directional Antenna Pattern Analyzer (DAPA), and Antena Meter software. Physic parameters of antenna considered to measure received signal strength (dBV/m), SWR ratio, antenna Gain, radiation angle. Those parameters measured using Spectrum Analyzer, MFJ antenna analyzer, and SWR meter. As measurement result from five omnidirectional antennas tested (G5, Telex, Dual-Band Supergainer, Larsen, Â¼ Lambda) obtained the most best performance showed by Telex antenna. And measurement result of two directional antennas tested (four element and five element) obtained the best performance shoed by five element antenna.